Memorias del 1.er Encuentro Iberoamericano de Economía Solidaria e Innovación Socioecológica - Toiber Rodríguez, Ingrid Anaid; Vargas Salcedo, Armando José; Orjuela Barberi, Fabio Nury; Astudillo Villegas, Ricardo; López Rodríguez, Alba Ligia; García Muller, Alberto; Garzón Olaya, Ana Beatriz; Ortiz Morales, Ana Lucrecia; Ramos Herrera, Antonio José; Luque González, Arturo; Hoinle, Birgit; Mina Varela, Carlos Alberto; et al. (Universidad Santiago de Cali, 2025)
Within the framework of strengthening the innovation and development ecosystem, scientific production plays a fundamental role in the economy of a territory, as it serves as the key element for cultivating knowledge as a generator of alternative solutions to face the challenges and issues present in today’s society. That being said, various spaces for the exchange of knowledge and best practices have been consolidated at both national and international levels, with the aim of encouraging the academic community to establish strategic alliances with organizations that integrate innovation processes to advance territorial competitiveness.